A Fatal Case of Klebsiella pneumoniae Mycotic Aneurysm. (29th November 2011) - Chao, Chien-Ming; Lee, Kun-Kuang; Wang, Chia-Sheng; Chen, Ping-Jen; Yeh, Tsung-Chih
Abstract : Mycotic aneurysm is a serious clinical condition with significant morbidity and mortality. Staphylococcus aureus and Salmonella species are the most common causative pathogens. Klebsiella pneumoniae was rarely reported as a possible pathogen causing mycotic aneurysm; therefore, we describe a K. pneumoniae -related fatal bacteremia mycotic aneurysm in a patient in spite of appropriate antimicrobial agents and surgical management.